TIME RESOLVED EVENTS ON THE REACTION PATHWAY OF TRANSCRIPT INITIATION BY A SINGLE SUBUNIT RNA POLYMERASE: RAMAN CRYSTALLOGRAPHIC EVIDENCE - Chen, Yuanyuan (2011)
The nucleotidyl transfer reaction leading to formation of the first phosphodiester bond has been followed in real-time by Raman microscopy, as it proceeds in single crystals of the N4 phage virion RNA polymerase (RNAP). The reaction is initiated by soaking NTP substrates and divalent cations into the RNAP and promoter DNA complex crystal, where the phosphodiester bond formation is completed in about 40 minutes. This slow reaction allowed us to monitor the changes of RNAP and DNA conformations as well as bindings of substrate and metal through Raman spectra taken every 5 minutes. Recently published snapshot X-ray crystal structures along the same reaction pathway assisted the spectroscopic assignments of changes in the enzyme and DNA, while isotopically labeled NTP substrates allowed differentiation of the Raman spectra of bases in substrates and DNA. We observed that substrates are bound at 2-7 minutes after commencing soaking, the O-helix completes its conformational change, and that binding of both divalent metals required for catalysis in the active site changes the conformation of the ribose triphosphate at position +1. These are followed by a slower decrease of NTP triphosphate groups due to phosphodiester bond formation that reaches completion at about 15 minutes, and even slower complete release of the divalent metals at about 40 minutes. We have also shown that the O-helix movement can be driven by substrate binding only. The kinetics of the in crystallo nucleotidyl transfer reaction revealed in this study suggest that soaking the substrate and metal into the RNAP-DNA complex crystal for a few minutes generates novel and uncharacterized intermediates for future X-ray and spectroscopic analysis.